VARIASI SOSIOLEK PADA MASYARAKAT DESA TIMU KECAMATAN TOMIA TIMUR KABUPATEN WAKATOBI - Halfian, Wa Ode; Afrianda, Afrianda; Masri, Fina Amalia (Seshiski: Southeast Journal of Language and Literary Studies, 2024)
Sociolect is a language variation that often occurs in communities from various circles. Age differences are one of the factors that influence the occurence of sociolect variations in the Timu Village community. To determine how the form of sociolect language variation can also be seen from the level of education, and researchers will describe the form of sociolect variation in The Timu Village community, East Tomia District, Wakatobi Regency. The type of this research was included in the type of field research with descriptive qualitative methods. The object of this research is sociolect in the daily conversation of the people in Timu Village, East Tomia Subdistrict, Wakatovi Regency. Data collection techniques in this research are observation technique, recording technique, listening technique, and note-taking technique. From the results of data analysis, the researchers found 12 data of sociolect variations in the Timu Village Community, East Tomia Subdistrict, Wakatobi Regency. Among them, there are sociolect variation in the form of slang 4 data, sociolect variation in the form of vulgarity 2 data, and sociolect variation in the form of colloquial 6.